HUBUNGAN ANTARA ADAPTABILITAS KARIER DAN KECEMASAN MENGHADAPI DUNIA KERJA PADA MAHASISWA TINGKAT AKHIR - Sharen Putri Tesalonia; Doddy Hendro Wibowo (Jurnal Cakrawala Ilmiah, 2023)
Final students are one of the seeds of human resources in the world of work. After graduating from college, they will face a greater challenge, namely entering the workforce. This condition gives the final student a difficult situation and causes anxiety in facing the world of work. Overcoming these feelings of anxiety, final students need to apply career adaptability when they want to enter the world of work. The research method used is a quantitative method with a correlational design. With a sample of 50 participants who were final year students in Salatiga, and used the Incidental Sampling technique. Data were collected using the Career Adapt-Abilities Scale (CAAS). The results showed that the value of Rxy = -0.11 and sig = 0.938 which means that there is a negative relationship between career adaptability and anxiety facing the world of work in final year students.